Implementation of Integrated Smart System Platform in Improving the Quality of Public Services through Smart Village In Pucangsari Village, Pasuruan Regency: Penerapan Integrated Smart System Platform Dalam Meningkatkan Kualitas Pelayanan Publik Melalui Smart Village Di Desa Pucangsari Kabupaten Pasuruan - Hakim, Lukman; Rosadi, Muhammad Imron; Prianto, Agus (Jurnal Soeropati, 2023)
The purpose of this service is to increase the knowledge and skills of the Pucangsari village government in the concept and implementation of a smart village based on an integrated smart system platform through village administration governance, reporting, and utilization of public service applications. The method used in the integrated smart system platform development program in village government services includes three stages; the first stage of preparation by conducting surveys and interviews related to the potential and problems faced by prospective program partners; the second stage of making and developing Integrated smart system Platform Applications; and the third stage of capacity building in the form of workshops, training and socialization. The results of this community service are increased knowledge related to smart villages, the ability to use integrated smart system platform applications and improved public services which include correspondence, billing and payment of land and building taxes, as well as the existence of a community aspiration space as an improvement in the Pucangsari village government performance system.